Strategi Pengembangan Budi Daya dan Pemasaran Ubi Jalar di Desa Sukajadi, Kecamatan Tamansari, Kabupaten Bogor - Kartika, Lindawati; Gunawan, Windi; Lubis, Lutfi Syahreza; Jouhary, Naufal Amir; Atsemani, Jezila Amana Nousra; Saputro, Ilham Tyas Sulistyo; Shinta, Karennina; Sukardi, Muhammad Mirza; Cantika, Silvi (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2024)
Sukajadi Village, located in Kecamatan Tamansari, Kabupaten Bogor, has significant agricultural land with the majority of its residents being farmers. Despite its high agricultural potential, most farmers still face various challenges such as traditional marketing methods, unstable crop prices, limited commodity variety, and lack of knowledge about cultivation techniques. One of the potential yet underutilized commodities is sweet potatoes. KKN-T IPB students designed the Agriwork program, a workshop on sweet potato cultivation and marketing techniques, in collaboration with the Agribusiness and Technology Park (ATP) of IPB University. This program aims to enhance farmers' understanding of effective cultivation and marketing techniques, and establish partnerships with ATP IPB University. The implementation of the program involved four main stages: socialization, land survey, assistance, and partnership. The Agriwork program successfully initiated partnerships between Sukajadi Village farmers and ATP IPB University. Three farmers from local farmer groups expressed interest in partnering, two of whom have undergone land surveys, and one has started planting seedlings. This partnership continues with the harvesting process of 3.5 tons of white and yellow sweet potatoes, supervised by ATP IPB University, and the preparation for signing the memorandum of understanding (MOU) between the farmers and ATP IPB. The AgriWork program by KKN-T IPB and ATP IPB supports Sukajadi farmers in improving sweet potato production and marketing. Three farmers became partners, receiving production assistance, price assurance, and access to modern markets, positioning Sukajadi as a potential sweet potato hub in Bogor.